Expression, purification and characterization of meta-cleavage enzyme CarBaBb from Novosphiongobium sp. KA1 (Journal of Biochemistry, Microbiology and Biotechnology, 2013)
The meta-cleavage enzyme CarBaBb of carbazole-degrader Novosphiongobium sp. KA1 were cloned, expressed and purified to homogeneity in Escherichia coli strain. The enzyme was cloned with 6x histidine residues attached at the C-terminal of large subunit CarBb for purification using affinity chromatography method prior to gel filtration chromatography. The CarBaBb, a two-subunit meta-cleavage enzyme, approximately 30 kda for CarBb dan 10 kDa for CarBa, was found to be Î±2Î²2-heterotetrameric (Mr 80,000), showed highest activity at pH 8.5 and temperature 30Â°C. CarBaBb showed highest catalytic activity towards 2,3-dihydroxybiphenyl with kcat/Km 4.1 M-1s-1, and overall higher catalytic activities towards biphenyl-type substrates in comparison to catechol-type substrates. Based on the similarities, this meta-cleavage enzyme from Novosphiongobium sp. KA1 would also be a good candidate for protein crystallization and structural studies apart from CarBaBb from strain P. resinovorans strain CA10.
Keywords: meta=cleavage enzyme; extradiol dioxygenase; carbazole; degradation